Temporal Patterns of N2O Fluxes From a Rainfed Maize Field in Northeast China - Su, Chenxia; Kang, Ronghua; Huang, Wentao; Fang, Yunting (Frontiers in Environmental Science, 2021)
Rainfed agriculture is one of the most common farming practices in the world and is vulnerable to global climate change. However, only limited studies have been conducted on rainfed agriculture, mainly using low-frequency manual techniques, which caused large uncertainties in estimating annual N2O emissions. In this study, we used a fully automated system to continuously measure soil N2O emissions for two years (April 2017 to March 2019) in a typical rainfed maize field in Northeast China. The annual N2O emissions were 2.8 kg N ha-1 in year 1 (April 2017 to March 2018) and 1.8 kg N ha-1 in year 2 (April 2018 to March 2019), accounting for 1.9% and 1.2% of the nitrogen fertilizer applied, respectively. The inter-annual variability was mainly due to different weather conditions encountered in years 1 and 2. A severe drought in year 1 reduced plant N uptake, leaving high mineral N in the soil, and the following moderate rainfalls promoted a large amount of N2O emissions. The seasonal pattern of N2O fluxes was mainly controlled by soil temperature and soil nitrate concentration. Both soil moisture and the molar ratio of NO/N2O indicate that N2O and NO were mainly derived from nitrification, resulting in a significant positive correlation between N2O and NO flux in the intra-rows (where nitrogen fertilizer was applied). Moreover, we observed that the N2O emissions during the freeze–thaw period were negligible in this region for rainfed agriculture. Our long-term and high-resolution measurements of soil N2O emissions suggest that sampling between LST 9:00 and 10:00 is the best empirical sampling time for the intermittent manual measurements.